2019
DOI: 10.29244/j.agromet.33.1.20-29
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Extreme Hydrological Index using HBV Model Simulation Results (Case Study : Upper Ciliwung Watershed)

Abstract: The study of climate change on hydrological response is a crucial as climate change impact will drive the change in hydrological regimes of river. Upper Ciliwung watershed is one of the critical rivers in Java Island, which has been affected by climate change. This study aims to: (i) simulate the discharge flow using the Hydrologiska Byrans Vattenbalansavdelning (HBV) model; (ii) simulate future flow using three general circulation models (GCM) namely Commonwealth Scientific and Industrial Research Organisatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
2
0
1
Order By: Relevance
“…Dalam kajian ini proses kalibrasi merupakan proses optimasi nilai parameter model, parameter model HBV yang telah dikalibrasi dapat dilihat pada Tabel 2 sedangkan debit hasil simulasi disajikan pada Gambar 5. Bizuneh et al, (2021) dan Lestari & Dasanto (2019).…”
Section: Optimasi Nilai Parameter Modelunclassified
“…Dalam kajian ini proses kalibrasi merupakan proses optimasi nilai parameter model, parameter model HBV yang telah dikalibrasi dapat dilihat pada Tabel 2 sedangkan debit hasil simulasi disajikan pada Gambar 5. Bizuneh et al, (2021) dan Lestari & Dasanto (2019).…”
Section: Optimasi Nilai Parameter Modelunclassified
“…With the increased recognition of the importance of feedback mechanisms between land surface processes and climate, there have been sustained efforts to develop more realistic land surface representations to be couple with the general circulation models (GCMs) (Boer et al, 2007;Lestari and Dasanto, 2019;Müller et al, 2021). The current generation of land surface models used in GCMs view the soil column as the fundamental hydrologic unit that effectively ignores the role of topography plays in the development of soil moisture heterogeneity and the subsequent impacts of this soil moisture heterogeneity on watershed evapotranspiration and the partitioning of surface fluxes (Rakovec et al, 2016).…”
Section: Recent Developments In Hydrological Modelingmentioning
confidence: 99%
“…Climate related studies in Indonesia showed that extreme weather events are closely related to various natural disasters, such as drought (King et al, 2016;Surmaini et al, 2018;Taufik et al, 2020Taufik et al, , 2017, floods (Lestari and Dasanto, 2019;Narulita and Ningrum, 2018), and frost (Pradana et al, 2018a(Pradana et al, , 2018b. The disasters influence many sectors in Indonesia specially the agricultural sector (Amalo et al, 2017;Kim et al, 2019;Kuswanto et al, 2019;Lesk et al, 2016;Mulyaqin, 2020), which indirectly affect national economic conditions (Boer and Surmaini, 2020;Chatzopoulos et al, 2020).…”
Section: Introductionmentioning
confidence: 99%